Respon Osmolaritas Udang Windu Penaeus monodon Fab. dalam Media Terkontaminasi Fenol - Haeruddin Haeruddin; Diana Rachmawati (Jurnal Perikanan Universitas Gadjah Mada, 2007)
Phenol represents nerve poison which able to cause paralysis due to the damage on fat tissue of nerve. In crustacean like tiger prawn, the damage on nervous system disturbs molting and osmoregulation activity, because both of those activities related to neuroendocrine system under control of center nervous system. This research was done to : (1) study the effect of various phenol concentration in culture medium to hemolymph osmolarity and osmotic work level of tiger prawn, (2) determine Low Observable Effect Concentration (LOEC) and No Observable Effect Concentration (NOEC) of phenol to hemolymph osmolarity and osmotic work level of the tiger prawn.The results showed that phenol has a significant effect on decreasing hemolymph osmolarity and increasing osmotic work level of tiger prawn. Osmolarity and osmotic work level respon pattern of the prawn to various phenol concentration is linear regression equation. NOEC and LOEC to the hemolymph osmolarity and the osmotic work level of the prawn are 0 to 2.08 mg/l and 2.08 mg/l, respectively.